Integration of Local Wisdom in Optimizing Socio-Culture Elementary School Students - Raden Ajeng Sofiyah; Beti Istanti Suwandayani; Maharani Putri Kumalasani (Universitas Majalengka, 2024)
Focusing on giving students a better understanding of who they are and the culture they live in, this study examines education that respects and values local wisdom. This is crucial for children's character development as well as preparing them to be globally competitive citizens who remain true to their cultural beliefs. This study aims to explore the integration of local wisdom in an effort to optimize social culture among elementary school students. Local wisdom, which includes the values, traditions and cultural practices typical of a community, plays an important role in the character building and social development of students. In the midst of rapid globalization and modernization, it is important to maintain and integrate local wisdom in the primary education curriculum so that students not only acquire academic knowledge but also understand and appreciate their cultural heritage. This research uses the Systematic Literature Review method with a case study approach in several primary schools that implement local wisdom in learning and extracurricular activities. The findings show that the integration of local wisdom can increase cultural awareness and social solidarity among students. Practices such as the introduction of folklore, traditional ceremonies and traditional crafts help students understand local values and apply them in daily interactions.